2021
DOI: 10.5712/rbmfc16(43)2655
|View full text |Cite
|
Sign up to set email alerts
|

Organization of primary health care in pandemics

Abstract: Background: The world is experiencing one of the greatest public health emergencies in history with the global spread of COVID-19. Health systems, including Primary Health Care (PHC) services, are pillars of pandemic coping strategies. Objective: To systematic review of the literature that analyzes the effectiveness of PHC organization strategies in the context of epidemics. Methods: We performed a rapid systematic literature review on MEDLINE (via PubMed), EMBASE and LILACS (via VHL), in order to analyze empi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
2
0
4
Order By: Relevance
“…Our results join with those of others 25 , 26 in supporting tailored policies to each community’s unique characteristics and needs, 25 particularly the needs of low income or rural populations. Primary care providers reported that provincial policies were insufficient in accounting for organizational and patient differences between communities and clinics during the pandemic.…”
Section: Discussionsupporting
confidence: 85%
“…Our results join with those of others 25 , 26 in supporting tailored policies to each community’s unique characteristics and needs, 25 particularly the needs of low income or rural populations. Primary care providers reported that provincial policies were insufficient in accounting for organizational and patient differences between communities and clinics during the pandemic.…”
Section: Discussionsupporting
confidence: 85%
“…Brasil tiene uno de los sistemas de salud universales más grandes del mundo, anclado en una extensa red de atención primaria de salud, pero que enfrenta problemas crónicos de financiación, gestión, suministro de personal y estructuración de servicios. 28 La APS es poderosa para reducir las inequidades en salud 29 y como lo refiere PerifaConnection (2020) citado por Sarti et al, (2020) 30 donde considera que la APS debe ser fortalecido y estructurado como una de las principales respuestas del sector salud a la epidemia, dado que está muy extendida en el territorio nacional y alcanza a importantes grupos de población expuestos a riesgos excesivos por sus condiciones de vida. Pandemias como la COVID-19 paralizan discursos y prácticas dirigidas a reducir el tamaño del Estado, flexibilizar las leyes laborales, desmantelar el sistema de protección social, menospreciar y reducir la inversión en ciencia, tecnología y educación, y socavar los servicios de salud pública.…”
Section: Resultsunclassified
“…(1) Nesse sentido, o bom funcionamento da APS objetiva superar o modelo hegemônico e promover uma assistência ampliada e integral à população. (2,3) Dentre os diversos campos profissionais que atuam no cotidiano dos serviços de saúde, a Enfermagem, representa hoje mais de 50% da força de trabalho do Sistema Único de Saúde, configurando-se assim em um dos pilares para a prática do cuidado. Em virtude das competências e habilidades desenvolvidas, as ações da enfermeira veem sendo decisivas no processo saúde-doença-cuidado ao considerar os determinantes sociais da saúde, iniquidades e condições crônicas, entre outros fatores que permeiam o bem-estar da população.…”
Section: Introductionunclassified